The Effect of Price, Promotion, and Ease of Use Application Online Transportation on the Usage Decision in Surabaya City - Fredianaika Istanti; Yuniawati Ekaningrum; Evada El Ummah Khoiro (Institute of Computer Science (IOCS), 2021)
The study aims to determine the effect of price, promotional appeal and ease of use of applications on the decision of use of online transportation. The type of research used in this study is